Integrated Transboundary Water-Climate Management Tools - Kgabi, Nnenesi (Water Security and Climate Adaptation in Southern Africa, 2020)
The scholarly theme of the book lends itself to the discipline of earth and atmospheric sciences, with a specific focus on water-climate studies. The book is a scholarly discourse by researchers in the natural sciences, including Hydrologists, Climate Scientists, Environmental Engineers and Water Scientists. The purpose of the book is to address the limited complementarity between the water and climate studies; which is crucial in promoting scientific research that informs policy decisions and implementation of water security plans. The chapters were selected to represent water-climate models and policy research conducted in different river basins in the arid and semi-arid environments. Therefore, the water-climate management tools highlighted in this book include General Circulation Models (GCMs), Coupled Model Inter-comparison Project Phase 5 (CMIP5), Soil and Water Assessment Tool (SWAT), Africa Flood and Drought Monitor (AFDM), Extreme Precipitation Events (EPEs), R ClimDex, Mixed strategy game models, Standard Precipitation Indices (SPIs), Water Evaluation and Planning System (WEAP), Penman Calculator, and Saturated Volume Fluctuation (SVF).